Visual Outcome And Complications After Cataract Surgery In Diabetic And Non-Diabetic Patients (Journal of Chittagong Medical College Teachers' Association, 2026)
Background: Cataracts are a leading cause of visual impairment globally, with higher prevalence and higher risks of complications with variable visual recovery among diabetic patients. The aim of the study is to compare the visual outcomes and postoperative complications of cataract surgery in diabetic versus nondiabetic  patients attending Chittagong Medical College Hospital (CMCH).Materials and methods: This prospective comparative study was conducted from January to December 2022 and included two groups: 104 diabetic and 105 nondiabeticpatients.Visual  acuity and complications were assessed preoperatively and at 1 week, 1 month and 3 months postoperatively. Data were analyzed using SPSS v25.Results: The diabetic group (n=104) had a significantly lower mean age (56.7±5.7 years) than the non-diabetic group (n=105) (60.4±6.3 years) (p